Regulatory Spillovers and Data Governance: Evidence from the GDPR - Peukert, Christian; Bechtold, Stefan; Batikas, Michail; Kretschmer, Tobias (Marketing Science, 2022)
Privacy regulation by the European Union has had effects for websites beyond the European Union and lead to an increase in market concentration of web technology vendors